ANALISIS PENGARUH PROJECT BASED LEARNING BERBASIS KODING TERHADAP KEMAMPUAN BERPIKIR KOMPUTASIONAL DAN KREATIVITAS SISWA KAJIAN LITERATUR - Wibowo, Andri; Nuni Widiarti; Decky Avrilianda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to systematically analyze the impact of Project-Based Learning (PjBL) integrated with coding on students' computational thinking (CT) and creative thinking skills. In the digital era, coding is no longer just a technical skill but a primary medium for fostering logical-mathematical and systematic reasoning. Using a Systematic Literature Review (SLR) method guided by the PRISMA framework, 15 relevant academic articles published between 2020 and 2025 were reviewed. The findings indicate that PjBL provides an authentic pedagogical environment that allows students to deconstruct complex phenomena through algorithmic design and mental modeling. The integration of tangible technologies, such as robotics and mobile programming, significantly enhances five dimensions of student competence: innovation, collaboration, critical analysis, algorithmic cognition, and problem-solving. Furthermore, meta-analysis results confirm that PjBL-based coding effectively bridges the gap between theoretical knowledge and practical application, fostering a more engaging and student-centered learning experience. This review provides a strategic framework for educators to implement coding-integrated PjBL to develop essential 21st-century higher-order thinking skills.